The Influence of Village Funds and Fund Allocations on Growth and Poverty in the Barlingmascakeb Area, Central Java Province - Aziz Dwian Nugroho; Albertus Maqnus Susilo; Akhmad Daerobi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This research is based on the magnitude of the influence of village funds, allocation of village funds on growth and poverty. This study aims to analyze the effect of village funds, village fund allocations on growth and poverty in the Barlingmascakeb Region. The analytical method used is path analysis. And to facilitate data processing, the analysis tool uses the Eviews version 9. For analysis purposes, secondary data is used in the form of time series data, 2017-2021, namely the amount of village funds, the total allocation of village funds, growth and poverty in the Barlingmascakeb Region. Data obtained from the Ministry of Finance, Central Java Statistics Agency and other sources, namely journals and research results  The results showed that the Village Fund had no significant effect on the poverty level. This result can be seen from the probability value of t count > 0.05. this shows that the Village Fund has no direct effect on the poverty level. The results showed that the Village Fund Allocation had no significant effect on the poverty level. This result can be seen from the probability value of t count > 0.05. This shows directly that the Village Fund Allocation has no influence on the poverty level. The results showed that Regional Economic Growth (GRDP) had no significant effect on the poverty level. This result was seen from the probability value of t count > 0.05. This shows that regional economic growth has no direct effect on poverty levels.